Erythropoietin directly stimulates osteoclast precursors and induces bone loss. Issue 5 (28th January 2015) - Hiram‐Bab, Sahar; Liron, Tamar; Deshet‐Unger, Naamit; Mittelman, Moshe; Gassmann, Max; Rauner, Martina; Franke, Kristin; Wielockx, Ben; Neumann, Drorit; Gabet, Yankel
ABSTRACT: Erythropoietin (EPO) primarily regulates red blood cell formation, and EPO serum levels are increased on hypoxic stress ( e.g., anemia and altitude). In addition to anemia, recent discoveries suggest new therapeutic indications for EPO, unrelated to erythropoiesis. We investigated the skeletal role of EPO using several models of overexpression (Tg6 mice) and EPO administration (intermittent/continuous, high/low doses) in adult C57B16 female mice. Using microcomputed tomography, histology, and serum markers, we found that EPO induced a 32%‐61% trabecular bone loss caused by increased bone resorption (+60%‐88% osteoclast number) and reduced bone formation rate (‐19 to ‐74%; P < 0.05 throughout). EPO targeted the monocytic lineage by increasing the number of bone monocytes/macrophages, preosteoclasts, and mature osteoclasts. In contrast to the attenuated bone formation in vivo, EPO treatment in vitro did not inhibit osteoblast differentiation and activity, suggesting an indirect effect of EPO on osteoblasts. However, EPO had a direct effect on preosteoclasts by stimulating osteoclastogenesis in isolated cultures (+60%) via the Jak2 and PI3K pathways. In summary, our findings demonstrate that EPO negatively regulates bone mass and thus bears significant clinical implications for the potential management of patients with endogenously or therapeutically elevated EPO levels.—Hiram‐Bab, S., Liron, T., Deshet‐Unger, N., Mittelman, M., Gassmann, M., Rauner, M., Franke, K., Wielockx, B., Neumann, D., Gabet, Y. Erythropoietin directly stimulates osteoclast precursors and induces bone loss. FASEB J. 29, 1890‐1900 (2015). www.fasebj.org